Redescription of the genus Koumansetta (Teleostei: Gobiidae), with description of a new species from the Red Sea - Kovačić, Marcelo; Bogorodsky, Sergey V.; Mal, Ahmad O.; Alpermann, Tilman J. (Zootaxa, 2018)
The gobiid genus Koumansetta Whitley, placed in synonymy by some authors with the similar genus Amblygobius Bleeker, is redescribed and its validity based on an integrated morphological and molecular assessment is confirmed. The following characters have been found that distinguish Koumansetta from any of 15 recognized valid species of Amblygobius: oculoscapular transverse rows trp and tra long, extending dorsally well above level of rows x1 and x2; snout pointed, prominent, longer than eye diameter, with gently sloping dorsal profile, overhanging mouth; mouth subterminal; the upper limb of first gill arch with 1–2 slender, weak and soft gill rakers anteriorly, followed by 1–5 short, also soft, broad structures; first two dorsal-fin spines elongate, remaining spines progressively shorter; pelvic frenum absent; body brown to brown-green in upper and lateral sides with narrow yellow or orange longitudinal stripes on body and head, black ocellated spot on the second dorsal fin, and another black spot dorsoposteriorly on caudal peduncle. The following three species are assigned to Koumansetta: K. rainfordi Whitley, the type species of the genus, known from the western Pacific Ocean; K. hectori (Smith), the most widespread species, known from islands of the western Indian Ocean to Micronesia and Fiji; and a new species, restricted to the Red Sea and the inner Gulf of Aden. Koumansetta hoesei sp. nov. has formerly been confused with similar K. hectori, but differs in various details of coloration, and in some morphological characters. Moreover, K. hoesei sp. nov. is evolutionary well divergent from K. rainfordi and K. hectori, its closest relative, as shown by phylogenetic analysis of the mitochondrial COI barcoding region. In addition to the description of the new species, brief species accounts are provided for K. hectori and K. rainfordi, and a key to the three species.